Association of airway obstruction with first-pass success and intubation-related adverse events in the emergency department: multicenter prospective observational studies - Takahashi, Jin; Goto, Tadahiro; Fujitani, Shigeki; Okamoto, Hiroshi; Hagiwara, Yusuke; Watase, Hiroko; Hasegawa, Kohei; , the Japanese Emergency Medicine Network Investigators (Frontiers in Medicine, 2023)
Background: Airway obstruction is a relatively rare but critical condition that requires urgent intervention in the emergency department (ED). The present study aimed to investigate the association of airway obstruction with first-pass success and intubation-related adverse events in the ED. Methods: We analyzed data from two prospective multicenter observational studies of ED airway management. We included adults (aged ≥18 years) who underwent tracheal intubation for non-trauma indications from 2012 through 2021 (113-month period). Outcome measures were first-pass success and intubation-related adverse events. We constructed a multivariable logistic regression model adjusting for age, sex, modified LEMON score (without airway obstruction), intubation methods, intubation devices, bougie use, intubator’s specialty, and ED visit year with accounting for patients clustering within the ED. Results: Of 7,349 eligible patients, 272 (4%) underwent tracheal intubation for airway obstruction. Overall, 74% of patients had first-pass success and 16% had intubation-related adverse events. The airway obstruction group had a lower first-pass success rate (63% vs. 74%; unadjusted odds ratio [OR], 0.63; 95% CI, 0.49–0.80), compared to the non-airway obstruction group. This association remained significant in the multivariable analysis (adjusted OR 0.60, 95%CI 0.46–0.80). The airway obstruction group also had a significantly higher risk of adverse events (28% vs. 16%; unadjusted OR, 1.93; 95% CI, 1.48–2.56, adjusted OR, 1.70; 95% CI, 1.27–2.29). In the sensitivity analysis using multiple imputation, the results remained consistent with the main results: the airway obstruction group had a significantly lower first-pass success rate (adjusted OR, 0.60; 95% CI, 0.48–0.76). Conclusion: Based on these multicenter prospective data, airway obstruction was associated with a significantly lower first-pass success rate and a higher intubation-related adverse event rate in the ED.